STUDI KOMPARASI KURIKULUM PENDIDIKAN BERBASIS PONDOK PESANTREN MATA PELAJARAN AGAMA ISLAM DI SMP PLUS EL-WAFA BEKASI DENGAN DI SMP ASY-SYARIFIYAH KARAWANG - Brillianty, Erilla Renggina; Salsabila, Athaya Hasna; Lindawati, Eneng; Arifudin, Yadi Fahmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study compares the implementation of the Islamic Boarding School-based Curriculum from two Junior High Schools (SMP) in selecting the Curriculum, subject placement, implementation of objectives in each school, use of methods in learning, and evaluation methods. This research uses a comparative study method by comparing two schools at the same level. The results of this paper explain the comparison of developments in the Islamic boarding school-based curriculum at the two junior high schools located in the general community environment.